The efficacy of cinnamon essential oil and vanillin in inhibiting Colletotrichum spp. and Fusarium spp. isolated from banana fruit: - - Chailert, Naphatsanan (Food and Applied Bioscience Journal, 2023)
Colletotrichum spp. and Fusarium spp. are the main fungi that cause of the postharvest loss of banana fruit loss during storage. In this study, poisoned food bioassay technique and vapor phase diffusion technique were used to investigate the inhibition effect of cinnamon EO (C) and cinnamon EO mixed with vanillin (VC) against Colletotrichum spp. and Fusarium spp. isolated from infected bananas tissue. For poisoned food bioassay technique, Colletotrichum spp. and Fusarium spp. were placed on potato dextrose agar containing 20, 100, 200 and 1000 μL/L of C and VC (vanillin 1 g/cinnamon EO 15 mL). The results showed that the growth of Colletotrichum spp. and Fusarium spp. were delay in PDA containing C and VC at 20 μL/L and above. Both strains were completely inhibited in PDA containing 100 μL/L C and VC and above. For the vapor phase diffusion technique, the 20, 100, 200 and 1000 μL of C and VC were dropped into sterile filter paper and adhered on the plate cover. At the lowest concentration studied, vanillin synergized the inhibition effect of cinnamon EO against both strains. VC had better antifungal effect against Colletotrichum spp. and Fusarium spp. compared with using C alone. Vanillin can be used to limit the stringent odour of cinnamon EO and helped to lower the amount of cinnamon EO required.